Tie-down cable-spring restrainers for seismic protection of isolated bridges. (October 2021) - Yi, Jiang; Li, Jianzhong; Tsang, Hing-Ho
Abstract: Seismic isolation has been a prevalent approach to seismic design of bridges whereas isolation bearings are susceptible to damages in a major earthquake event. A tie-down cable-spring restrainer (TCR) is therefore proposed to protect isolated bridges under near-fault ground motions. The proposed TCR transmits large horizontal force to the substructure under large earthquakes while does not compromise isolation efficiency of the isolator under small ones. The key concepts and theoretical model are provided in this article and a design procedure is put forward for the application of TCR to a bridge with lead-rubber bearings. Case studies show that seismic isolation and ductile behavior develop sequentially under large earthquakes and the isolators are well protected from excessive displacement. It is found that bridges with TCRs have larger displacement capacity and show less sensitivity to near-fault ground motions.